IMPROVEMENT OF METHODOLOGICAL FACILITY TO TEACHING PEDagogy - Mahliyo Khaydarova (Scholar Express Journal, 2023)
This article is written about the improvement of methodological preparation for teaching the science of education. Today, the main goal of methodical training of future teachers to teach the science of education is to make the young generation mature in all respects, well-rounded people necessary for the development of our society.
Keywords: elementary education; elementary educationpedagogical process; uchitel